A COMPARATIVE EVALUATION OF INTERNATIONAL ROUGHNESS INDEX (IRI) TECHNIQUES BETWEEN MOBILE LASER SCANNER (MLS) AND DIPSTICK - Tri Saksena, Heru; Adikusuma, Taufik Nur (Jurnal Jalan Jembatan, 2025)
Assessing road surface quality is essential for maintaining and ensuring the safety of transportation infrastructure. This study evaluates the effectiveness of Mobile Laser Scanning (MLS) using the Leica Pegasus TRK 700 Evo in comparison to the conventional Dipstick method for measuring the International Roughness Index (IRI) on road surfaces. IRI data were collected from five sample locations, with observed differences between the two methods ranging from 0.02 m/km to 1.00 m/km and an average deviation of 0.19 m/km. The results suggest a high degree of compatibility between the IRI values generated by both methods, indicating that MLS can serve as a reliable alternative for road condition surveys. The Leica Pegasus TRK 700 Evo demonstrated operational efficiency, capable of surveying 40 to 100 kilometers of road per day under typical field constraints, such as equipment setup and GNSS base station relocation every 15 kilometers. Data processing required approximately four hours for every hour of field measurement. A field deployment scenario was developed, detailing the necessary resources, including a survey vehicle equipped with the MLS unit (staffed by a driver, operator, and section owner), a support vehicle for high IRI zones, a GNSS base station transport vehicle, and a two-person data processing team. The findings demonstrate that MLS technology is a practical and efficient tool for road condition assessment and offers a flexible, reliable alternative to traditional survey techniques in managing transportation infrastructure. Keywords: International Roughness Index (IRI), Mobile Laser Scanning (MLS), point cloud, road condition, road assessment.